2020
DOI: 10.1186/s12937-020-00594-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of gender-targeted versus gender-neutral interventions aimed at improving dietary intake, physical activity and/or overweight/obesity in young adults (aged 17–35 years): a systematic review and meta-analysis

Abstract: Background: Young adulthood has become synonymous with the development of poor lifestyle behaviours associated with an increased risk of preventable chronic disease in later years. Interventions aiming to improve health behaviours may be more engaging and effective if they are targeted to males or females than interventions with a gender-neutral approach. This review will examine the outcome effectiveness of gender-targeted and gender-neutral interventions targeting nutrition, physical activity or overweight/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 119 publications
(244 reference statements)
0
31
1
1
Order By: Relevance
“…Likewise, it must be pointed out that the time of sedentary physical activity corresponds to the periods in which the 40 volunteers costaleros is resting. In turn, the data show that men are more active than women [22][23][24]. These data differ from the study carried out on English adults (40-69 years of age) [25] in which it is noted that women are less sedentary than men.…”
Section: Physical Activity Intensitycontrasting
confidence: 85%
“…Likewise, it must be pointed out that the time of sedentary physical activity corresponds to the periods in which the 40 volunteers costaleros is resting. In turn, the data show that men are more active than women [22][23][24]. These data differ from the study carried out on English adults (40-69 years of age) [25] in which it is noted that women are less sedentary than men.…”
Section: Physical Activity Intensitycontrasting
confidence: 85%
“…Following publication of the original article [1], the authors would like to correct the mix up in intervention groups when reporting results of one paper in the third paragraph under the heading Physical activity outcomes.…”
mentioning
confidence: 99%
“…Second, most foods(such as whole grains, tubers, vegetables and bean) in this pattern have a low glycaemic load, which has been reported to be associated with a lower risk of T2DM [38].Third, our nding also indicated that participants who belonged to the fourth quartile of grains-vegetables pattern had a higher level of physical activity, compare to those in the lowest quartile. A recent meta-analysis of observational studies revealed that higher level of physical activity was associated with decreased risk of obesity, a major factor for diabetes [39].…”
Section: Discussionmentioning
confidence: 99%